Gambaran pengetahuan dan sikap karyawan PT Wenang Cemerlang Press terhadap kekerasan dalam rumah tangga - Ruslani, Ajeng Kartika; Siagian, Iyone E. T.; Ottay, Ronald I. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2017)
Objective: The Mass Media plays an important role in conveying the information either through the electronic media as well as print media, this research aims to find out how the knowledge and attitude of the employees of PT Wenang Cemerlang Press against domestic violence.Methods: This research is a descriptive qualitative research with cross sectional design research. With the Focus Group discussion using a purposive sampling, and in-depth interview technique, which consists of 10 informant and the informant's 10 taken 5 informant to do in-depth interviews.Results: The informants agree that men are very instrumental in absorbing the acts of domestic violence.Conclusion: Overall knowledge of employees and attitude of PT Wenang Cemerlang Press about domestic violence already is quite good because it can explain the definition, form, and domestic violence.Keyword: knowledge, attitudes, employee, domestic violence